ePortfólios como recursos de carreira – programa online com estudantes do ensino superior - Henriques, Susana (2024)
The ‘B4C - Boost for Career’ aims to promote and/or improve the employability of higher education students by focusing on career resources. It was designed and delivered in a digital environment to students from two Portuguese public higher education institutions. As part of the course, each participant developed an e-portfolio as an employability support and assessment tool. In this article, we present and discuss the results of the thematic content analysis of the 151 e-portfolios developed in the two editions of ‘B4C’. The thematic analysis was guided on the one hand by the themes that emerged from the theoretical framework, namely career resources, and on the other hand by their operationalisation by the participants. The main findings show that while the programme developed specific competences related to career resources and others such as digital competences, it also raised awareness of the importance of career resources from the perspective of integrating or managing complex career paths.